(untitled) - Kaplinsky, Raphael (Sussex, Canada, 2000)
The purpose of this document is to put into the public domain methods and materials to help researchers support the development of value chains targetted especially at enabling poor communites to engage more actively in value chains. It includes many useful resources and methods.
Kinh doanh nông nghiệp
Keywords: Business logistics,Quản trị kinh doanh